THE EFFECT OF NUMERICAL LITERACY LEARNING MODEL ON THE FIFTHGRADE STUDENTS’ MATHEMATICS LEARNING OUTCOMES AT SD NEGERI 156320 SIMPANG TIGA 2 - Reno Francius Simanullang1; Patri Janson Silaban; Dyan Wulan Sari H.S; Darinda Sofia Tanjung; Juliana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the effect of applying the numerical literacy learning model on students’ mathematics learning outcomes in the material of collecting and presenting data in class V at SD Negeri 156320 Simpang Tiga 2 in the academic year 2022/2023. The research uses a quantitative research method. The research population consists of 30 fifth-grade students of SD Negeri 156320 Simpang Tiga 2, comprising 16 male students and 14 female students. The sampling technique used is purposive sampling, which was applied to class V with a total of 30 students. The research results indicate that students’ learning outcomes using the numerical literacy learning model are categorized as good, with an average score of 77.96 and a correlation test result of 0.983. This means that rcount (0.983) ≥ rtable (0.361), therefore Ha is accepted. Thus, there is a very strong influence between the use of the numerical literacy learning model and students’ mathematics learning outcomes in the material of collecting and presenting data in class V at SD Negeri 156320 Simpang Tiga 2. This finding is further supported by the results of the t-test, where tcount (28.266) ≥ ttable (1.697), indicating that Ha is accepted. It shows that there is a significant positive effect of using the numerical literacy learning model on students’ mathematics learning outcomes in the material of collecting and presenting data in class V at SD Negeri 156320 Simpang Tiga 2 in the academic year 2022/2023.